Leitura literária de alunos do campus São Mateus do Instituto Federal do Espírito Santo frente às tecnologias de informação e comunicação contemporâneas - Rubim, Rossanna dos Santos Santana (2016)
This study aimed at identifying and analyzing practices and representations of literary reading of a group of students from Instituto Federal do Espírito Santo, campus São Mateus, in order to understand how these readers present themselves, and collect impressions of their literary readings appropriations using contemporary information and communication technologies that present themselves as a support for the written word (printed material, smartphones, tablets, e-readers, notebooks). To this end, it has had as its main contribution what Roger Chartier states about the notions of practices, appropriations and representations, taking into consideration the material issues and the establishment of reading protocols inherent to the constitution of the mentioned supports. This is a study focused on the reader, more particularly his practices, representations and appropriations of literary reading, and its theoretical and methodological feasibility arises from the questioning developed during the second half of the twentieth century the paradigm that gave the author and / or the text the primacy in the meaning production process. This research is also driven by further discussions as the field of Theory of Literature becomes interested in the ways through which readers are inscribed in the texts and mobilize them. This study was exploratory and it was configured as a case study. Considered an exploratory research, this work is configured as a case study. In this matter, it was conducted documental research, and a field data collection, through questionnaire application and conduction of a focus group with students of the mentioned institution. The study of the collected data contributed to the identification of reading practices of a predominantly young audience, whose literary preferences meet the current tastes of a globalized and integrated network society, that appropriates textual media in different formats, but selects them also considering the textual genres, showing that the literature representations are strongly related to the printed support. As a conclusion, the research points to a community of individuals with hybrid reading practices.